Inhaled CO2 vs. Hypercapnia Obtained by Low Tidal Volume or Instrumental Dead Space in Unilateral Pulmonary Artery Ligation: Any Difference for Lung Protection? - Spinelli, Elena; Pesenti, Antonio; Lopez, Gianluca; Damia, Anna; Damarco, Francesco; Garbelli, Erica; Dal Santo, Gaia; Caccioppola, Alessio; Giudici, Giorgio; Figgiaconi, Virginia; Biancolilli, Osvaldo; Battistin, Michele; et al. (Frontiers in Medicine, 2022)
Background: Unilateral ligation of the pulmonary artery (UPAL) induces bilateral lung injury in pigs undergoing controlled mechanical ventilation. Possible mechanisms include redistribution of ventilation towards the non-ligated lung and hypoperfusion of the ligated lung. Addition of 5% CO2 to the inspiratory gas (FiCO2) prevents the injury, but it is not clear whether lung protection is a direct effect of CO2 inhalation or it is mediated by plasmatic hypercapnia. Aim of this study was to compare the effects and mechanisms of FiCO2 vs. hypercapnia induced by low tidal volume ventilation or instrumental dead space. Methods: Healthy pigs underwent left UPAL and were allocated for 48 hours to: volume-controlled ventilation (VCV) with VT 10 ml/kg (Injury, n = 6); VCV plus 5% FiCO2 (FiCO2, n = 7); VCV with VT 6 ml/kg (low VT, n = 6); VCV plus additional circuit dead space (instrumental VD, n = 6). Histological score, regional compliance, wet-to-dry ratio and inflammatory infiltrate were assessed to evaluate lung injury at the end of the study. In order to investigate the mechanisms of protection, we quantified the redistribution of ventilation to the non-ligated lung, as the ratio between the percentage of tidal volume to the right and to the left lung (VT RIGHT/ LEFT), and the hypoperfusion of the ligated lung as the percentage of blood flow reaching the left lung (PerfusionLEFT). Results: In the left ligated lung, injury was prevented only in the FiCO2 group, as indicated by lower histological score, higher regional compliance, lower wet-to-dry ratio and lower density of inflammatory cells compared to other groups. For the right lung, histological score was lower both in the FiCO2 and in the low VT groups, but the other measures of injury showed lower intensity only in the FiCO2 group. VT RIGHT/ LEFT was lower and PerfusionLEFT was higher in the FiCO2 group compared to other groups. Conclusions: In a model of UPAL, inhaled CO2 but not hypercapnia grants bilateral lung protection. Mechanisms of protection include reduced overdistension of the non-ligated and increased perfusion of the ligated lung.